REVENUE RECOVERY AT PT. XYZ - Oliveira Samosir, Ramos
The painting and blasting industry in Indonesia has always been associated with the maritime industry. But more broadly than that, almost all objects made of iron will definitely intersect with painting and blasting. PT. XYZ is a company engaged in this industry by providing painting and blasting application services. Given the level of this company which can still be considered a small-scale family company, plus the COVID-19 pandemic that has hit the past few years, it has reduced the income that PT. XYZ. Besides that, the development of PT. XYZ is also low year over year.